Wprowadzenie - Markowski, Dariusz (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2010)
The present number of AUNC “Conservation and Restoration Studies,” as the previous one, contains articles devoted to both the issues of the history of art, and the technology and conservation of monuments. The author undertaking the issues of the history of art is Małgorzata Geron, whose paper is devoted to the Vision of the city in the artistic output of Leon Chwistek. Geron has pointed out in it to the fact, that in the output of that artist, being also an eminent mathematician, philosopher and theoretician of art, since the year 1917 involved in the Formists Group, exists a group of works touching upon the problems of modern city. The author has made an attempt to prove that that theme is of a very coherent character and covers both the works of art and literary works as well as theoretical texts. In her paper Picture frame in service interior design the author, Katarzyna Wantuch-Jarkiewicz, pointed out to exceptionally important role played by picture frame in the surrounding interior, to its more or less auxiliary position towards such elements as the architecture or furniture. Two articles are devoted to the research issues regarding arts’ technology and techniques: Non-invasive method of the in situ identifi cation of pigments – the analysis of oil paintings by Jozef Pankiewicz with portable XRF - spectroscope by Mirosław Wachowiak and Mirosław Sawczak and Application of UV- fl uorescence microscopy in identifi cation of characteristic features of the structure of oil paintings by Aleksander Gierymski by Zuzanna Rozłucka and Ewa Doleżyńska-Sewerniak. The authors of the fi rst text discuss the results of the analysis of elementary composition of selected pigments of the paint layer of 39 oil paintings by Jozef Pankiewicz, dated back to the years 1888 –1938 withthe portable XRF - spectroscope. The analysis allowed also to determine the composition of priming, extenders added to the paints as well as the base for organic red. The authors stressed the non-invasiveness of the method in comparison with the methods used so far for identifi cation of elementary composition of pigments as well as the possibility to obtain information on the elementary composition of lower strata, depending on the permeability of the upper ones. The authors of the second study presented the research on the structure of selected oil paintings by Aleksander Gierymski (1850 –1901), based on the microscopic analysis of samples of paint layers. The research covered samples from ca. 30 works of the artist, representing all periods of his artistic activity. According to the authors the applied method of UV -fl uorescence microscopy allowed for determination of characteristic features of the structure of paintings, mainly the binders and the way they were used. Among the studies discussing conservation issues, often related to the analysis of materials, evaluation of condition as well as the course of conservation treatment one can fi nd three papers. The research on technology of mortars imitation Gotland and Obernkirchen natural stones has been written by Wiesław Domasłowski, who on commission of Deutsches Bergbau- Museum Zollern-Institut in Bochum (Germany) conducted series of tests aiming for the development of technology of the making of mortars, that would have physical and chemical properties matching those of Gotland and Obernkirchen sandstones. The criteria assumed by the author were capillary properties and compression resistance. The paper by Teresa Łękawa- Wysłouch Reintegration of priming injuries in paintings on canvas – the review of materials and methods presents an overview of the literature on reintegration of priming injuries in paintings on canvas. The author paid special attention to the criteria of choosing the materials used in this process, characterised the means applied and discussed the methods of handling them during the whole procedure, starting from preparation of the putty, its application, levelling the surface and developing the texture. In the article Some technological procedures that may contribute to the failures and imperfection of tanned leather Tomasz Kozielec pointed out the fact, that hide, before it becomes a ready to use product (tanned leather) must undergo a series of diverse stages of processing. In 19th century, when tanning developed into industry, speeding the technological processes caused lowering of the quality and durability of that raw material. The author discussed a number of factors having negative infl uence on the properties of leather end-products. Editors of the presented volume, like of the previous one, have consciously publish diverse articles, touching upon the issues of broadly understood history of art and conservation of monuments. One should hope for its contents to be a valuable and fruitful reading, that would contribute to broadening the knowledge on arts, both in the fi eld of theory, research and conservation treatment.